International asymmetries and the design of the international financial system - Ocampo, José Antonio (ECLAC SantiagoCL, 2001)
Argues that the design of the international financial system should take into consideration three different problems that the current system faces viz. financial market instability; basic macroeconomic and financial asymmetries that characterize the international economy; and the additional problems generated by the imcomplete and asymmetric nature of the current globalization process.